EVALUATION OF FERMENTED CORN COB MEAL AS A CARBOHYDRATE SOURCE IN CARP (Cyprinus carpio) - Fadillah Fadillah; Sahrul Alim; Andre Rachmat Scabra (Universitas Mataram, 2026)
Carp (Cyprinus carpio) is one of the freshwater commodities with the highest production and is widely cultivated in Indonesia. From 2010 to 2017, carp production increased by 33,954 tons. This increase in production will be accompanied by an increase in feed demand in fish farming. The high price of feed is a constraint in the cultivation process. Therefore, other alternatives are needed to reduce feed production costs, such as the utilization of agricultural waste. The agricultural waste used was corn cobs fermented using cow rumen fluid. The study was conducted with the aim of analyzing the use of fermented corn cob meal as a carbohydrate source for carp (Cyprinus carpio). The method used in the study was an experimental method using a Completely Randomized Design (CRD) with 5 treatments with different doses and 3 replications. The treatments given consisted of P1 (control, without corn cob meal), P2 (25% TBJ substitution), P3 (50% TBJ substitution), P4 (75% TBJ substitution), and P5 (100% TBJ substitution). The results showed that the substitution of corn meal with corn cob meal had a significant effect on P5 with an absolute weight value of 3.57 g, and an absolute length of 1.30 cm. Meanwhile, the survival rate parameter of 73.3% had no significant effect between treatments. So, the use of fermented corn cob meal up to 100% can be used to increase carbohydrate utilization without reducing growth performance in carp.